An investigation of national policies on transformational government (t-Gov) in Europe. (1st January 2014) - Parisopoulos, Konstantinos; Tambouris, Efthimios; Tarabanis, Konstantinos
Electronic government (e-government) is high in the agenda of a large number of countries worldwide for more than a decade now. Recently, the concept of transformational government (t-Gov) was introduced to determine the stage of e-government evolution characterised by the radical restructuring of the public sector towards efficiency. The aim of this paper is to understand t-Gov and investigate the level of t-Gov sophistication in Europe by assessing the e-government policies of 18 European Union member states. We first review the relevant literature, to conclude t-Gov embraces nine defining elements namely user-centric services, joined-up government, one-stop government, multichannel service delivery, flexibility, efficiency, increased human skills, organisational change and change of attitude of public servants, and value innovation. We also review e-government assessment frameworks that could be used to evaluate t-Gov sophistication. We thereafter critically examine and compare the degree of t-Gov sophistication of 18 European Union member states. Here, the results suggest that most strategies partially only exploit the full potential of t-Gov. For example, all strategies address user-centric services and most address efficiency, breaking out of silos, and joined-up government. On the other hand, however, no policy addresses constant value creation and value innovation and only a few address flexibility and organisational change and change of attitude. Using a published e-government assessment framework we finally compare progress across Europe with regards to t-Gov.